2018
DOI: 10.1111/hsc.12590
|View full text |Cite
|
Sign up to set email alerts
|

NonPharmacological interventions for managing wandering in the community: A narrative review of the evidence base

Abstract: Dementia-related wandering is exhibited by as many as 63% of people with dementia living in the community. There is strong evidence that people with dementia who wander are at risk of life-threatening outcomes including injury from falls, exhaustion, weight loss, and becoming lost. Furthermore, carers have reported that fear of a person with dementia becoming lost contributes to them taking extreme measures in an attempt to maintain safety at home and there are few guidelines to direct care practices. Previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 49 publications
2
6
0
Order By: Relevance
“…This change in the care-giving role was a natural transition that emerged from the need to support their loved one move into TESA and emerged from the ‘hitting the crisis point’ theme where ICs identified the provision of safety as a key issue. For example, in line with other reported research (Brittain et al, 2017; MacAndrew et al, 2018), ICs’ responses to wander walking were particularly stressful, with some ICs feeling morally conflicted by the methods required to avoid risks that emerged by wander walking. This is an important finding for two reasons.…”
Section: Discussionsupporting
confidence: 77%
“…This change in the care-giving role was a natural transition that emerged from the need to support their loved one move into TESA and emerged from the ‘hitting the crisis point’ theme where ICs identified the provision of safety as a key issue. For example, in line with other reported research (Brittain et al, 2017; MacAndrew et al, 2018), ICs’ responses to wander walking were particularly stressful, with some ICs feeling morally conflicted by the methods required to avoid risks that emerged by wander walking. This is an important finding for two reasons.…”
Section: Discussionsupporting
confidence: 77%
“…Although the selected products were similar, usability ratings by dyads of product B were significantly better than ratings of product A throughout the study. Differences in ratings of usability and design features within dyads are in line with previous studies, which have suggested that the needs and preferences of PwDs and CGs with GPS devices need to be taken into consideration as they may differ [7,8,42,43]. Also, the finding that usability ratings with both products decreased after 4 weeks of use, but not significantly, seems to imply that users' expectations could not be fully met, but that they were not entirely dissatisfied.…”
Section: Discussionsupporting
confidence: 87%
“…In spite of the mentioned limitations, this study provides a starting point for research on UX and clinical effectiveness with wearable GPS devices. Future studies using a randomized mixed-method dyadic approach with standardized and validated outcome measures are needed [43] , [53] .
Research in Context Systematic review: The authors reviewed all relevant publications on the user experience and clinical effectiveness with wearable global positioning system (GPS) devices for persons with dementia (PwDs) and caregivers (CGs) using PubMed, meeting abstracts, and presentations.
…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations